2016
DOI: 10.1002/jat.3413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral exposure to the phthalate substitute acetyl tributyl citrate on female reproduction in mice

Abstract: Acetyl tributyl citrate (ATBC), is a phthalate substitute used in food and medical plastics, cosmetics, and toys. Although systemically safe up to 1000 mg/kg/day, its ability to cause reproductive toxicity in females at levels below 50 mg/kg/day has not been examined. This study evaluated the effects of lower ATBC exposures on female reproduction using mice. Adult CD-1 females (n=7–8/treatment) were dosed orally with tocopherol-stripped corn oil (vehicle), 5 or 10 mg/kg/day ATBC daily for 15 days, and then bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 22 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…BPF exposure (20 – 500 mg/kg/day) did not alter estrous cycles in rats (Higashihara et al 2007). In contrast, DEHA (1,000 and 2,000 mg/kg/day) decreased average estrous cycle length in rats (Wato et al 2009) and ATBC (5 mg/kg/day) decreased average estrous cycle length in mice (Rasmussen et al 2016). …”
Section: Plasticizer Alternativesmentioning
confidence: 89%
See 2 more Smart Citations
“…BPF exposure (20 – 500 mg/kg/day) did not alter estrous cycles in rats (Higashihara et al 2007). In contrast, DEHA (1,000 and 2,000 mg/kg/day) decreased average estrous cycle length in rats (Wato et al 2009) and ATBC (5 mg/kg/day) decreased average estrous cycle length in mice (Rasmussen et al 2016). …”
Section: Plasticizer Alternativesmentioning
confidence: 89%
“…DEHA (1,000 and 2,000 mg/kg/day), a phthalate alternative, increased atresia in preantral and antral follicles (Miyata et al 2006; Wato et al 2009). ATBC (5 and 10 mg/kg/day), a phthalate alternative, decreased the numbers of primordial, primary, and secondary follicles, but did not alter the numbers of corpora lutea or atretic follicles in mouse ovaries (Rasmussen et al 2016). In contrast the BPA analogue, BPF (20 – 500 mg/kg/day), did not cause histopathological changes in the rat ovary (Higashihara et al 2007).…”
Section: Plasticizer Alternativesmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies link bisphenol A exposure to aromatase inhibition in granulosa cells and delay or suppression of LH surge resulting in modified ovarian cyclicity (Viguié et al 2018 ). Di-(2-ethylhexyl) adipate can shorten the average length of the estrus cycle in rats (Wato et al 2009 ), whereas acetyl tributyl citrate has been shown to do so in mice (Rasmussen et al 2017 ). In humans, exposure to organophosphate pesticides has been related to a higher risk of irregular menstrual cycles and shorter menstrual bleed duration among Chinese women (Zhang et al 2019 ).…”
Section: Adverse Outcome Pathways As They Relate To Key Processes In mentioning
confidence: 99%
“…Tributyl citrate (TBC) is usually applied as a thermally stable, high-performance, and nontoxic plasticizer in toys, medical products, biodegradable polymers, and food additives [1][2][3][4]. Moreover, TBC is a biorenewable and sustainable plasticizer.…”
Section: Introductionmentioning
confidence: 99%